AWARENESS AND PRACTICES OF EPILEPTIC CARE AMONG SPECIAL EDUCATORS FOR EPILEPSY - Ghazala Usman (ziauddin University, 2024)
Background: Epilepsy is a common but usually stigmatized disease due to its presentation therefore; the awareness of care givers regarding epilepsy is crucial for better management and upbringing of child. This study aims to assess the degree of apprehension among special educators, as epilepsy is more prevalent in special children. Method: A cross-sectional study using questionnaire, based on interviews by 56 participants from numerous special schools of Karachi was conducted. Results: All special educators knew about epilepsy through their relevant courses. 85.7% of them dealt with the epileptic person directly during their practice. They explained epileptic attack as period of seizure (71.5%), period of loss of consciousness (64.3%), and memory loss (35.7%). 57.1% perceived causes of epilepsy to be inherited, as oxygen deficiency during birth46.4%, as birth defect46.4%, stroke 42.9% and 39.3% believe brain tumor can be the cause. Perceived triggers were (71.4%) emotional disturbance, (67.9%) stress, (53.6%) sleep deprivation and (60%) skipping medicine. Unfortunately, 7% of them consider epilepsy as contagious disease. 11% thinks epilepsy is some kind of spiritual possession or black magic. 30% stated that epileptics should be treated by Hakims while 25% believes quacks can cure it. Conclusion: Overall knowledge was adequate and attitude was positive toward epileptic children. Favorably, 70 to 80% of them supported the idea that people with epilepsy can get good education and take up a job and even can marry and have family life.